2016
DOI: 10.1055/s-0042-103422
|View full text |Cite
|
Sign up to set email alerts
|

Successful endoscopic closure of a gastrocutaneous fistula using a ‘Padlock Clip’

Abstract: Gastrocutaneous fistula closure using an endoscopically deployed Padlock Clip (Aponos Medical Corp., Kingston, New Hampshire, USA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…This device is conceptually similar to the Ovesco system, but has some features which make it very attractive. Few studies have reported on the efficacy of this device in clinical practice 7 8 9 . Considering the emerging role of these devices in clinical practice, we decided to describe our experiences with this novel OTSC system in the treatment of gastrointestinal wall defects and EFTR.…”
Section: Introductionmentioning
confidence: 99%
“…This device is conceptually similar to the Ovesco system, but has some features which make it very attractive. Few studies have reported on the efficacy of this device in clinical practice 7 8 9 . Considering the emerging role of these devices in clinical practice, we decided to describe our experiences with this novel OTSC system in the treatment of gastrointestinal wall defects and EFTR.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the first OTSC system introduced was the Ovesco Clips (Ovesco Endoscopy AG, Tübingen, Germany) followed by the more recently developed Padlock Clip which offered a more affordable alternative and possibly equal success in managing gastrointestinal fistulas which had no prior intervention (16)(17)(18). Additionally, there were two reported cases of failed rectovesical and rectocutaneous fistula closure with the Ovesco clips that were subsequently managed with the Padlock Clips.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the Padlock Clip has been described for recurrent bleeding and esophageal fistula (5 patients) [12], closure of a gastrocutaneous fistula (2 patients) [13,14], and esophageal stent fixation (1 patient) [15]. We present the largest series for its use for eFTR.…”
Section: Discussionmentioning
confidence: 99%